IMPROVING THE MECHANISM OF BRAND FORMATION IN THE FASHION INDUSTRY (Scientific Journal of Actuarial Finance and Accounting, 2024)
The article mainly provides information about the formation of the brand and the mechanisms of development in the fashion industry. In today's advanced age, creating and improving the brand of each industry plays an important role. Therefore, in the article, the formation of the brand, its orientation to the market, as well as economic indicators are relevant. The work of foreign scientists and the activities of modern fashion industry enterprises were also analyzed.